2012
DOI: 10.1021/op3000064
|View full text |Cite
|
Sign up to set email alerts
|

Initial Process Development and Scale-Up of the Synthesis of a Triple Reuptake Inhibitor ALB 109780

Abstract: Early process development toward a triple reuptake inhibitor is described. Three different routes were evaluated; one of them was optimized and scaled up to generate 470 g of API as this route minimized the formation of undesired side products. The selected route featured Eaton’s reagent-mediated cyclization of a phenyl acetamide, copper-mediated Buchwald–Hartwig coupling to install a morpholine moiety, and palladium-catalyzed α-arylation of a dihydroisoquinolinone to construct the core structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Yang and co‐workers68 studied the synthesis of α‐arylated THIQs (tetrahydroisoquinolines) by α‐arylation of 63 . A catalyst generated from Pd(OAc) 2 and BINAP as the ligand in dioxane gave 65 in 98.8 % isolated yield.…”
Section: Syntheses Involving α‐Arylation Of Carboxyamides and Lactamsmentioning
confidence: 99%
“…Yang and co‐workers68 studied the synthesis of α‐arylated THIQs (tetrahydroisoquinolines) by α‐arylation of 63 . A catalyst generated from Pd(OAc) 2 and BINAP as the ligand in dioxane gave 65 in 98.8 % isolated yield.…”
Section: Syntheses Involving α‐Arylation Of Carboxyamides and Lactamsmentioning
confidence: 99%
“…On the basis of its most potent and balanced triple inhibition profile and weak CYP2D6 inhibition profile, compound 10i was advanced for profiling in a number of in vitro and in vivo assays. An ex vivo binding assay was used to measure the transporter occupancy levels in rodent brain .…”
Section: Resultsmentioning
confidence: 99%
“…ALB109780 (353) is a triple-reuptake inhibitor that could lead to improved treatment for depression, 205 for which Yang et al at AMRI reported a robust synthetic route (Scheme 72). 206 The discovery route was successfully used to prepare ∼150 g of drug substance ALB109780 (353). However, this route was deemed not suitable for larger scale production, mainly because of the formation of two des-bromo impurities 356 and 357 during the two Pd-catalyzed cross-coupling reactions that required extensive column chromatographic purifications to remove.…”
Section: Applications In Route Design Process Development and Scale-u...mentioning
confidence: 99%